2019
DOI: 10.4014/jmb.1811.11042
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Interleukin-21 Production by Optimization of Codon and Signal Peptide in Chinese Hamster Ovarian Cells

Abstract: Interleukin-21 is a common γ-chain cytokine that controls the immune responses of B cells, T cells, and natural killer cells. Targeting IL-21 to strengthen the immune system is promising for the development of vaccines as well as anti-infection and anti-tumor therapies. However, the practical application of IL-21 is limited by the high production cost. In this study, we improved IL-21 production by codon optimization and selection of appropriate signal peptide in CHO-K1 cells. Codon-optimized or non-optimized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Signal peptides play a significant role in recombinant protein production. Several studies have suggested that using artificial signal peptides can improve the expression and secretion of a recombinant protein (19)(20)(21)(22)(23)(24). Importantly, altering signal peptide sequences is designed to change binding to the signal recognition particle, which ideally should not affect the characteristics of a recombinant protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Signal peptides play a significant role in recombinant protein production. Several studies have suggested that using artificial signal peptides can improve the expression and secretion of a recombinant protein (19)(20)(21)(22)(23)(24). Importantly, altering signal peptide sequences is designed to change binding to the signal recognition particle, which ideally should not affect the characteristics of a recombinant protein.…”
Section: Discussionmentioning
confidence: 99%
“…These included antibody signal peptides from Ig heavy chain signal peptide 7 and Igκ light chain signal peptide 1, that exhibit the best secretion for 4 antibodies out of the 5 in CHO K1 cells, including Avastin, Remicade, Rituxan and Humira (19), and also from murine Igκ light chain, that shows 1.5-fold as effective as the expression of recombinant human coagulation factor VII using native signal peptide in CHO K1 cells (20). We also selected signal peptides derived from human albumin, that increases antibody production in CHO K1 cells by 50-60% compared to control signal peptide (21), and from human azurocidin 1, that increases recombinant interleukin-21 production in CHO K1 cell media by 7-fold compared to native signal peptide (22). In addition, we selected signal peptides from human serine protease 2 and human chymotrypsinogen B1, that proved to be 14.2-fold and 11.8-fold as effective as that of human albumin for recombinant Gaussia luciferase production in CHO cells (23).…”
Section: Introductionmentioning
confidence: 99%
“…Signal peptides have been engineered to improve the affinity to the SRP, which correlates with the translocation efficiency and yield of the recombinant protein. The azurocidin signal peptide was found to increase IL-21 secretion approximately 2.5-fold and the Ig κ signal peptide to enhance the expression of recombinant coagulation factor VII 1.5fold in CHO cells (Cho et al, 2019;L. Peng et al, 2016).…”
Section: Engineering Translation and Traffickingmentioning
confidence: 95%
“…Signal peptides have been engineered to improve the affinity to the SRP, which correlates with the translocation efficiency and yield of the recombinant protein. The azurocidin signal peptide was found to increase IL‐21 secretion approximately 2.5‐fold and the Ig κ $\kappa $ signal peptide to enhance the expression of recombinant coagulation factor VII 1.5‐fold in CHO cells (Cho et al, 2019; L. Peng et al, 2016). Similarly, optimization of the signal peptide mediating secretion of antibodies in CHO cells resulted in an increase in the yields of anti‐HER2 antibody (Herceptin, 2.2‐fold), anti‐CD20 antibody (Rituxan, 2‐fold), and anti‐VEGF‐A antibody (Avastin, 3‐fold) (Haryadi et al, 2015; You et al, 2018).…”
Section: The Synthetic Biology Toolbox For Optimizing the Expression ...mentioning
confidence: 99%
“…In addition, understanding the presence or absence of SPs in the genes of interest is critical for choosing the appropriate recombinant protein expression and purification systems, as the intracellular accumulation of secretory proteins and toxins may be toxic to the host cells. Indeed, the ability of SPs to translocate proteins has been utilised in recombinant protein expression systems for high quality and quantity results (Futatsumori-Sugai and Tsumoto, 2010; Cho et al ., 2019; Karyolaimos et al ., 2019; Peng et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%